Cam jansen and the millionaire mystery eaudiobook - Adler, David A. (Cam Jansen, 2013)
Young people far and wide are enthralled by David A. Adler's Cam Jansen - the pint-sized sleuth with a photographic memory. In Cam's 32nd adventure, she and her best friend Eric Shelton find themselves at a fundraising luncheon for local firefighters. When the host's valuable necklace disappears, Cam is hot to jump on the case. But with every guest a suspect, can Cam solve the crime before the guilty party gets away?